KONTRIBUSI POWER OTOT TUNGKAI TERHADAP KEMAMPUAN LARI 100 M SISWA SMP NEGERI 2 KUBU - ', Sukartono; ', Saripin; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is about low the result of 100 m running ablitiyi students of SMPN 2 Kubu. This is presumably because of leg muscles power. Therefore, the purpose of this study was to determine whether there is a contribution leg muscles power to 100 m running ability students of SMPN 2 Kubu. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is a leg muscle powers and while the dependent variable (Y) is 100 m running ability. The research data was obtained from the standing broad jump test and 100 m running. Based on the results of research and data processing using statistical procedures of research, it can be concluded that the presence of a meaningful relationship between leg muscles power to 100 M running, the mark with 0.77 rhit> rtab 0.374, with a contribution of 59%.Keywords : Leg Muscles Power, 100 m, Running